2020
DOI: 10.1021/acsami.0c12042
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Therapy Using Codelivery of Cisplatin and Glutathione Peroxidase Targeting siRNA from Iron Oxide Nanoparticles

Abstract: Glioblastoma (GBM) is the most common and lethal type of malignant brain tumor in adults. Currently, interventions are lacking, the median overall survival of patients with GBM is less than 15 months, and the postoperative recurrence rate is greater than 60%. We proposed an innovative local chemotherapy involving the construction of gene therapy-based iron oxide nanoparticles (IONPs) as a treatment for patients with glioblastoma after surgery that targeted ferroptosis and apoptosis to address these problems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…This necessitates an urgent need to explore new therapeutic targets to improve the effectiveness of GBM treatment. Increasing iron levels in GBM cells in various ways to induce ferroptosis in tumor cells now appears to be an effective therapeutic approach [ 11 , 49 ]. Our finding of the induction of the COPZ1-based ferroptosis signaling pathway in GBM provides a new possibility for treatment of this disease and possibly others, as COPZ1 also appears to play an important role in the occurrence and development of other types of solid tumors based on analysis of related databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This necessitates an urgent need to explore new therapeutic targets to improve the effectiveness of GBM treatment. Increasing iron levels in GBM cells in various ways to induce ferroptosis in tumor cells now appears to be an effective therapeutic approach [ 11 , 49 ]. Our finding of the induction of the COPZ1-based ferroptosis signaling pathway in GBM provides a new possibility for treatment of this disease and possibly others, as COPZ1 also appears to play an important role in the occurrence and development of other types of solid tumors based on analysis of related databases.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting iron-related proteins or increasing intracellular iron levels are considered to be feasible strategies for treating cancers [ 9 , 10 ]. Our recently published work also found that inducing ferroptosis in GBM can achieve good therapeutic effects [ 11 ]. However, an understanding of the molecular mechanisms involved in the process in GBM will help to exploit ferroptosis in the treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was also adopted by Chen et al to design cisplatin-loaded Fe 3 O 4 /Gd 2 O 3 hybrid nanoparticles with conjugation of lactoferrin and RGD dimer (FeGd-HN@Pt@LF/RGD2), which could release cisplatin, Fe 2+ , and Fe 3+ after endocytosis in the endosomes, leading to high inhibition efficacy on orthotopic brain tumors (Shen et al, 2018). Ni et al synthesized FA/Pt+si-GPX4@IONPs for gene treatment of glioblastoma (Zhang et al, 2020b). The cascade reactions triggered by Pt laid the foundation for efficient ROS production to induce a combination of ferroptosis and apoptosis.…”
Section: Cascade Reactions Increased Rosmentioning
confidence: 99%
“…Recently, increasing evidences have verified that ferroptosis correlates with progression and therapeutic response of glioma ( Lang et al, 2019 ; Tang R. et al, 2020 ; Xu Y. et al, 2020 ). The dysregulation of ferroptosis-related genes (for example, GPX4, SLC7A11, and ACSL4) was found capable of protecting glioma cells from ferroptosis ( Wang et al, 2018 ; Cheng et al, 2020 ; Zhang et al, 2020 ). Erastin, a ferroptosis inducer, has been reported to have temozolomide (TMZ)-sensitizing effect on glioma cells ( Chen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%